The Gospel in the Womb of Culture: Between Syncretism and Orthodoxy in Christian Mission Spirituality and Contemporary Mission - Tampilang, Risno (Sekolah Tinggi Teologi Sriwijaya, 2024)
Main issue discussed in this study is the tension between the Gospel and culture in the context of contemporary Christian missions. Often, efforts to proclaim the Gospel are seen as conflicting with local cultural values, creating a dilemma between syncretism and orthodoxy. The aim of this research is to offer an alternative understanding that bridges this tension through an incarnational concept, and to explore how the Gospel and culture can mutually interpolate without losing their respective essences. The methods used are literature review and theological-missional analysis, focusing on the incarnational understanding as an approach in Christian missions. This study explores various theological and missiological perspectives to formulate a alternative understanding of the relationship between the Gospel and culture. The findings show that an incarnational approach allows for dynamic dialogue and interaction between the Gospel and culture. The Gospel can become a renewing agent that purifies the positive aspects of culture, while culture provides a contextual